Implementation and Performance Analysis of Internet Networks for RT/RW Using MikroTik and OpenWRT in Simalidu Koto Salak Dhamasraya - Putra, Aldo Aditya; Dewi, Ratna; Setiawan, Herry (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research analyzes the implementation and performance of RT/RW Net Internet networks utilizing MikroTik and OpenWrt in Simalidu Koto Salak, Dharmasraya, addressing the significant challenges posed by the region's telecommunications infrastructure. The primary objective is to evaluate critical Quality of Service (QoS) parameters that greatly influence user experience, specifically focusing on bandwidth, throughput, delay, jitter, and packet loss. Employing a systematic methodology, the study begins with site surveys to assess geographical and infrastructural contexts, followed by the deployment of a Point-To-Point network system designed to ensure optimal signal quality and efficient user management through MikroTik devices. Findings reveal that QoS in the RT/RW Net network is considerably affected by both technical configurations and the quality of the signal, culminating in a QoS score of 3.5, which corresponds to a 75% performance rating. These results indicate that, while the implemented network solution meets basic connectivity needs, further optimization is crucial to enhance user satisfaction and overall performance. Consequently, the study offers several recommendations aimed at improving internet service quality in similar environments, highlighting the necessity of continuous evaluation and adaptation of network configurations to meet the evolving demands of users. Furthermore, it suggests that future research could delve into advanced technologies and methodologies to further enhance network performance and user experience, particularly in rural areas, thereby effectively addressing connectivity challenges and ensuring that the benefits of reliable internet access are widely distributed among local communities.